Comparison of McDonald jars and plastic strainers for the artificial incubation of red tilapia eggs - Tush C., Justaquio (Zamorano: Escuela Agrícola Panamericana, 2016, 2016)
Tush, J. 2008. Comparison of McDonald jars and plastic strainers in the artificial incubation of red tilapia eggs. Graduation Project (Thesis) of the B. S. Program in Agricultural Science and Production, Pan-American School of Agriculture, Zamorano, Honduras. Often the development and expansion of fish farming is limited by the lack of good quality seed. An alternative to enhance fry production is to implement artificial incubation systems for fertile tilapia eggs removed from the buccal cavity of the adult females. The objective of this study was to compare McDonald jars and plastic strainers in the artificial incubation of red tilapia eggs in Zamorano, Honduras. Eggs were collected weekly from adult female red tilapia managed in concrete tanks as part of the fish reproduction program at the Aquaculture Station. Eggs were held in four McDonald jars placed within a water recirculation system, or in four plastic strainers in all-glass aquaria with static water, during seven-day long incubation periods repeated four times during a five-week period. The experimental design consisted of two treatments (McDonald jars and plastic strainers) and four replicates of each. Tilapia eggs from multiple clutches were distributed randomly in all containers. The number of eggs surviving in each incubation system was compared by an ANOVA (P<0.05). The results recorded for water quality was within the acceptable range for tilapia fry rearing. The results demonstrate that the artificial incubation of red tilapia eggs under conditions in Zamorano is feasible and high levels of survival can be attained after only a few weeks of practice. Most mortality occurred during the first half of each seven-day incubation period and the trends were similar between the two types of systems. Average survival during the 5th week was significantly greater for the eggs incubated in the plastic strainers (95.3%) compared to eggs from the McDonald jars (82.3%).